Efektivitas Pemberian Pakan Sistem Indeks Terhadap Laju Pertumbuhan dan Kualitas Air Pada Budidaya Udang Vaname (L. vannamei) - Handajani, Hany; Taqwa, Brilian Amanat; Hariyadi, Hariyadi (Jurnal Perikanan Unram, 2025)
Inefficient feeding in vannamei shrimp (Litopenaeus vannamei) cultivation has a negative impact on growth and water quality. The purpose of this study was to determine the effectiveness of index system feeding on growth rate and water quality in vannamei shrimp (L. vannamei) cultivation. The research method used was descriptive, the data were analyzed using the t-test statistical test. The parameters tested in this study were growth parameters including Average Body Weight (ABW), Average Daily Growth (ADG), Feed Conversion Ratio (FCR), and Survival Rate (SR). Water quality parameters include temperature, pH, Dissolved Oxygen (DO), salinity, ammonia, nitrite, nitrate, and Total Organic Matter (TOM). The results showed that there was a significant difference between the feeding index system and the anco check system. The index system is more effective in increasing the growth rate and the Feed Conversion Ratio (FCR) and Survival Rate (SR) results are obtained according to the optimum value. In the index system the average Average Body Weight (ABW) is 14.24 ± 0.68, the average Daily Growth (ADG) is 0.43 ± 0.02, the average Feed Conversion Ratio (FCR) is 1.06 ± 0.04, and the average survivak rate (SR) is 70.75 ± 5.56%. Whereas in the anco check system the average Average Body Weight (ABW) is 12.1 ± 1.13, the average Daily Growth (ADG) is 0.35 ± 0.04, the average Feed Conversion Ratio (FCR) is 1.18 ± 0.07 and the average survival rate (SR) is 59.25 ± 5.12%. Water quality during maintenance obtained optimum results according to the optimum standard of water quality for vannamei shrimp (L. vannamei) cultivation. Feeding the index system gives better results for the growth rate in vannamei shrimp farming, so that the feed given is more effective and efficient.